Filtration-enrichment methods for selecting auxotrophs and other mutants in Ascobolus immersus and similar filamentous fungi. - B. C. LAMB; S. HELMI (Fungal Genetics Reports, 1991)
Filtration-enrichment is a very successful method for obtaining auxotrophs, but traditional methods cannot be applied directly to many fungi lacking suitable asexual spores, mainly because of a heavy carry-over of parental nutrients into sexual spores. A procedure has been devised to apply filtration-enrichment to such fungi by using hyphal mutagenesis, crossing, germination of sexual spores, fragmentation of germination hyphae into small propagules, and then two cycles of filtration-enrichment in liquid minimal medium (LMM).